The Impact of the Job Creation Law on the Protection of Wages for Fixed-Term Employment Workers (PKWT) - Jakariya, Jakariya; Hardyansah, Rommy; Darmawan, Didit (Bulletin of Science, Technology and Society, 2024)
This research discusses the impact of changes in wage regulations for Fixed-Term Employment Agreement (FTEA) workers in Indonesia following the implementation of the Job Creation Law (Law Number 11 Year 2020). The main objective of the law is to create labor market flexibility and improve economic competitiveness, but the changes have created significant problems for FTEA workers, especially in terms of unfair wages and uncertainty regarding their rights. The removal of several wage provisions that previously provided protection, as well as reduced oversight of fair wage implementation, worsened the bargaining position of FTEA workers. This research also evaluates the legal impact of these new regulations on workers' rights and suggests the need for strengthened oversight and more proactive policies to protect FTEA workers from exploitation and wage injustice.